An Experimental Investigation of PAH Emissions from a Heavy Duty Diesel Engine Fuelled with Biodiesel and its Blend - Shah, Asad Naeem; shan, G. E. Yun-; wei, TAN Jian-; Zhi-hua, Liu (Biological Sciences - PJSIR, 2008)
. For the comparison of emissions of polycyclic aromatic hydrocarbons (PAHs) from diesel, biodiesel and its 20% blend with diesel, and their carcinogenic potencies, an experimental study has been conducted on a turbocharged, intercooled and direct injection diesel engine. Total PAHs (solid and gas) from diesel, B20 and B100 at low load were more than those at high loads. Total PAH emissions from the test fuels at the rated speed were more than those at maximum torque speed. Benzo[a] pyrene (BaP) brake specific emission of biodiesel is less than that of diesel. LMW-PAH emissions for the test fuels are all higher than those of MMW and HMW PAH. Biodiesel and B20 reduce both the total Benzo[a]pyrene equivalent concentration (BaPeq) and the total mean–PAHs as compared to commercial diesel fuel. BSFC of the engine increased but its brake power decreased in the cases of B20 and biodiesel.